Bladder filling before accreta surgery is a very effective method for preventing bladder injury: a retrospective cohort study. (3rd July 2021) - Celik, Samettin; Celik, Handan; Soyer Calıskan, Canan; Tosun, Miğraci; Hatirnaz, Safak
Abstract: Objectives: The aim of this study is to show whether bladder filling with saline before percreta surgery diminish the rate of bladder injuries or not. A secondary aim was to check the operative and postoperative outcomes between the cases of filled and unfilled bladder in placenta accreta surgery. Methods: This retrospective multicentric cohort study involved 88 patients who were diagnosed with placenta accreta and underwent cesarean hysterectomy between 1 January 2009 and 1 January 2019. Women who had cesarean hysterectomies due to the indication of placenta accreta and did not have bladder filling were used as the control group. Results: Eighty-eight women met the inclusion criteria. Forty-nine of the cases, the bladder was filled with saline solution before the operation, whereas in 39 the bladder was not filled. Intraoperative bladder injury occurred less in patients with preoperative filled bladders than in patients with unfilled bladders ( p  = .015; p  < .05). There was a statistically significant difference between the duration of surgery according to bladder inflation ( p  = .001; p  < .01); in the filled bladder group, the operation time was shorter than in the unfilled group. Conclusions: Filling the bladder with 200 ml saline solution before starting a cesarean section is an easy and useful technique that can reduce the possibility of bladder injury in placenta accreta surgery.